Beyond Cultural Persistence: Decolonizing Identity Through Local-Global Encounters in An Island Society of Eastern Indonesia - Marlon Edison Leatemia; Paulus Koritelu; Piter Jacob Pelupessy (Universitas Pattimura, 2026)
This study challenges the dominant “cultural persistence” paradigm in Global South sociology, which often portrays local communities as passive custodians of tradition under globalization. Focusing on the Patasiwa Putih community in Amahai, Eastern Indonesia, it examines how local identity is actively decolonized through dynamic local–global encounters. The study explores (1) the construction of identity through indigenous structures and symbols (2) its transformation under globalization, modernization, and digital technology, and (3) the strategies through which local actors negotiate and reconstruct identity. Employing a qualitative case study, data were collected through in-depth interviews, participant observation, and document analysis involving customary leaders, community members, and youth. The analysis follows an interactive model supported by triangulation and member checking. Findings reveal that identity is not eroded but reflexively transformed through reinterpretation of cultural symbols, ritual revitalization, and selective adaptation to global influences. While rooted in customary institutions, identity expands through digital mediation and generational shifts, producing a dynamic interplay between continuity and change. This study advances a decolonial perspective by reframing identity as an active and emancipatory process and highlights island societies as critical sites of knowledge production in the Global South.